The Interactions Between Antibiotic Resistance Genes and Heavy Metal Pollution Under Co-Selective Pressure Influenced the Bio-Enzyme Activity - Qi, Zheng; Qi, Yue; Le, Zhiwei; Han, Furui; Li, Fang; Yang, Hong; Zhang, Tielin; Feng, Yajie; Liu, Rijia; Sun, Yuan (Frontiers in Chemistry, 2021)
The spread of antibiotic resistance genes (ARGs) has brought potential risks to public health. However, the interactions between heavy metals and ARGs, as well as their potential effect on bio-enzyme activity under the pressure of co-selectivity in soil still remain poorly understood. In this work, the distribution characteristics and the co-selective relationship of 28 ARGs and eight heavy metals in soil in a dairy farm were visualized via the geographic information system (GIS) technique. Eight kinds of heavy metals were detected by an atomic fluorescence spectrometer and atomic absorption spectrophotometer, which were further evaluated via the single factor pollution index value. The GIS analysis showed that arsenic (As) was the key element responsible for soil pollution, which was found to be positively related to soil depths. The top three comprehensive scores of ARGs ranked the orders of sul2 > tetX > blaTEM, indicating the high potential of risk caused by these genes in the soil environment. In addition, the functional predications performed with the 16 SrDNA sequencing data based on the KEGG database indicated that the sulfonamides in soil involved multiple pathways, especially the metabolism, transport and catabolism, and membrane transport processes. This suggested that most bio-enzymes were found to be expressed in low activities in different pathways. Significant correlations were observed between the heavy metals and ARGs (p < 0.05), particularly between the ARGs and As, Cu, Ni, Pb, and Zn (p < 0.01). This study offers deep insights into the potential interactions between heavy metals and ARGs in soil and provides guidance for the fabrication of enzyme-based smart materials for soil remediation in dairy farms.